Changes in Liver Function and Lipid Profile during Underactive Thyroid Phase in Patients after Subtotal Thyroidectomy: Changes in Liver Function and Lipid Profile during Underactive Thyroid Phase - Haq, Zainab; Shayan Zaidi, Syed Usama; Umar, Muhammad; Ali, Muhammad Shazib; Waseem, Ali Bin; Imran, Areeba; Shahid, Muhammad Nauman (Pakistan Journal of Health Sciences, 2024)
Underactive Thyroid Phase or Hypothyroidism is a very common biochemical complication after sub-total thyroidectomy. Objectives: To investigate lipid profile and liver function in patients who developed hypothyroidism following sub-total thyroidectomy. Methods: Total 100 individuals were selected for present study and divided them into two different groups i.e. Group-A in which 37 healthy individuals were placed whereas in Group-B 63 individuals were adopted surgical process, sub-total thyroidectomy. The study was conducted in Surgical and Medical Units of Ghurki Trust & Teaching Hospital, Lahore from December 2023 to April 2024. Thyroid-stimulating hormone (TSH) levels were extremely high in individuals in the hypothyroid stage. Results: The comparative findings of this study showed a significant (p < 0.05) change in cholesterol, triglyceride, LDL and HDL blood serum levels of Group-B individuals as compared to the Group-B. While a significant (p < 0.05) amplification in enzymes of liver such as aspartate aminotransferase (AST), alanine transaminase (ALT), and decrease in alkaline phosphatase (ALP) in Group-B subjects were seen as compared to normal individuals. Conclusions: Sub-total thyroidectomy is associated with hypothyroidism, which correlates with disruptions in liver enzyme activity and lipid metabolism, potentially leading to secondary hyperlipidemia and liver dysfunction.